Futurable: Serious game to raise awareness by building futures - Jules Sekedoua Kouadio; Manon Borgne; Irène Langlet; Mounissamy Alice; Joachim Müller; Fanny Barnabé; Helène Sellier (Global Journal of Ecology - Peertechz Publications, 2023)
Today, educational uses of games (serious games) and gamification companies are multiplying, which are helping to extend the field of games so that "the idea of games comes to apply to realities, to situations, to behaviors in connection with which its use, until recently, would have seemed inappropriate, even absurd or scandalous'. However, all these systems are based on very diverse educational and political models, constructing their public sometimes as receivers to be trained, consumers to be convinced, workers to be hired or citizens to be mobilized. This article makes it possible to present and analyze a concrete case of mediation and awareness-raising through play, in which the playful experience is articulated with the fictional creation of anticipation in an attempt to support an open form of democratic dialogue about cities and territories' evolution regarding climate change issues. This game that was developed is analyzed through this article.